THE GROWTH AND YIELD OF SOYBEAN ON SHOOT CUTTING TIME AND APPLICATION OF GROWTH REGULATORS - Sagala, Danner; Hidayat, Haris Rifki; Prihanani, Prihanani; Asfaruddin, Asfaruddin (University of Prof. Dr. Hazairin, SH, 2025)
This research aimed to determine the effect of shoot cutting combined with spraying growth regulators on the growth and yield of soybeans. The experiment was arranged in a factorial randomized block design and was repeated three times. Shoot cutting treatments were performed 10, 20, and 30 days after planting. The growth regulators applied were Cytokinin, Auxin, and Gibberellin. The growth and yield of soybean plants were observed through plant height, number of branches, percentage of canopy coverage, leaf area, number of pods, weight of 100 seeds, and number of seeds per plot. The results showed that the interaction of the two treatments had no significant effect on soybean growth and yield. The Gibberellin treatment significantly affected plant height at 6 weeks after planting, number of branches at 4 weeks after planting, number of pods, and yield per plot.